Overexpression and purification of a fimbria-associated adhesin of Streptococcus parasanguis. - Oligino, L (1993)
A Streptococcus parasanguis adhesin that blocks the attachment of S. parasanguis FW213 to saliva-coated hydroxyapatite (SCHA) has been purified. Previous work demonstrated that the attachment of FW213 to SCHA is mediated by fimbriae and that one component associated with fimbriae is a 36-kDa protein (FimA) that reacts with antifimbria serum in Western blots (immunoblots) and is not present in afimbriated mutants. To obtain amounts of FimA sufficient for adhesion blocking assays, we cloned the gene coding for FimA into an Escherichia coli T7 overexpression system. The resulting strain produced large amounts of FimA, as much as 50% of the total cell protein. FimA was purified by elution from sodium dodecyl sulfate-polyacrylamide gels, and its native conformation was reestablished by sodium dodecyl sulfate removal, resolubilization in guanidine hydrochloride, and 50-fold dilution. Some refolded FimA aggregated into dimers and trimers. Preincubation of SCHA with 100 micrograms of purified, renatured FimA per ml blocked 85% of the binding of FW213. The FimA-SCHA complex was quite stable and could be washed continuously for at least 2 h with only a slight loss of FimA blocking activity. When FimA was added to preformed bacterium-SCHA complexes, it displaced 40% of the bacteria already bound to SCHA. The results suggest that FimA is an adhesin with a high substrate affinity and may prove useful in the development of a therapeutic agent for the prevention of plaque formation and endocarditis initiated by the sanguis streptococci.